Do in-work benefits work for low-skilled workers? - Bruno Van der Linden (IZA World of Labor, 2016)
High risk of poverty and low employment rates are widespread among low-skilled groups, especially in the case of some household compositions (e.g. single mothers). “Making-work-pay” policies have been advocated for and implemented to address these issues. They alleviate the above-mentioned problems without providing a disincentive to work. However, do they deliver on their promises? If they do reduce poverty and enhance employment, can we further determine their effects on indicators of well-being, such as mental health and life satisfaction, or on the acquisition of human capital?
Keywords: J08; J30; J32; 330; making work pay; inactivity trap; redistribution; single mothers; earned income tax credit; working tax credit